Cracking of enigma of Evans: a rare association with Sjogren and systemic lupus erythematosus - Prakash Kumar, Gyan; Bari, H. M. Faizul; Ratan, Piyush; Mishra, Tanya; Kumar, Ashutosh; Jha, P. N.; Kumar, Ashok (International Journal of Research in Medical Sciences, 2024)
Evans syndrome (ES) is characterized by the simultaneous or consecutive occurrence of warm autoimmune hemolytic anemia (AIHA) along with immune thrombocytopenia (ITP), and less commonly, autoimmune neutropenia. It may manifest spontaneously or as a result of autoimmune, malignancy or lymphoproliferative disease. Clinical manifestations may be associated with hemolysis and thrombocytopenia, potentially leading to life-threatening outcomes. ES is a rare diagnosis of exclusion. Due to its infrequency, the treatment is typically empirical, relying largely on intravenous corticosteroids or immunoglobulins. We are presenting case of a 46-year-old- female with bleeding from the mouth and gums and rashes all over the body with no prior diagnosis of rheumatological disorder. This case is pivotal as it highlights a key factor contributing to ES and presents a pragmatic method for addressing the condition.